Sumber Daya Manusia Generasi Z di Era Artificial Intelligence: Menggabungkan Kreativitas, Teknologi dan Kewirausahaan (Pengabdian Masyarakat pada SMA Muhammadiyah 3 Bungah, Gresik) - Alamudi, Abdul Kadir (JURNAL PENGABDIAN MANAJEMEN, 2025)
The advancement of Artificial Intelligence (AI) and digital transformation has significantly impacted the world of work, education, and entrepreneurship. Generation Z, as digital natives, faces challenges in adapting quickly to these changes, particularly due to low AI literacy, limited 21st-century skills, and lack of early entrepreneurial exposure. This community service program aimed to equip student of SMA Muhammadiyah 3 Bungah, Gresik, with relevant knowledge, skill, and mindset through an IPTEKS-based approach (Science, Technology, and the Arts). The method employed was participatory and experiental, starting from needs assessment, module development, to the implementation of seminars, business simulation, and mentoring sessions. The results showed significant improvement in students’ understanding of AI, their confidence in presenting ideas, and their ability to collaborate. These finding indicate that contextual education in technological literacy and entrepreneurship is and effective strategy for preparing young human resources to become adaptive, creative, and competitive in the digital disruption era.